YIELD OF WHEAT CULTIVARS IN FUNCTION OF TRINEXAPAC-ETHYL AND NITROGEN RATES - BERTI, Melissa; ZAGONEL, Jéferson; FERNANDES, Eliana Cuéllar (Scientia Agraria, 2007)
With the aim of determine the rate and the time of ethyl-trinexapac application in wheat cultivars experiments was established at the UEPG School Farm in Ponta Grossa, PR, in 2005. The experimental design was a complete randomized blocks, in a factorial scheme 2 x 2 x 6, with three repetitions for each wheat cultivars. The treatments consisted of nitrogen rates (50 and 240 kg ha-1), time of trinexapac-ethyl application (between first and second node and between second and third perceivable node) and trinexapac-ethyl rates (0; 31,2; 62,5; 93,7; 125,0 and 156,2 g ha-1). It was evaluated agronomical characteristics, diseases severity and yield. The increase of the nitrogen rate resulted in the increase of the yield for CEP-24 cultivar; the most delayed time of application of trinexapac-ethyl affects positively the yield of CD-104 and CEP-24 cultivars; trinexapac-ethyl reduced the plants height of all the cultivars; for all the cultivars the equation of the yield in relation to the trinexapac-ethyl rates was quadratic, occurring an increase of the yield with the increase of the reducer rate, until a limit (since 63,8 to 132,5 g ha-1), variable with the cultivar.